Avian Diversity and Abundance in the Machhaplan Complex, Hetauda, Nepal - Bhusal, Nahakul (FORESTRY: Journal of Institute of Forestry, Nepal, 2021)
Avifaunal survey was carried out in Machhaplan Complex, Hetauda from December 2020 to April 2021. The objective of the study was to assess the avian species diversity, richness and abundance. A total of 164 bird species belonging to 19 orders and 59 families were recorded by using Point Count Method. Out of these, 117 species were terrestrial and 47 species were wetland dependent. Passeriformes and Muscicapidae were the most dominant orders and families, respectively with 73 and 12 species. The most abundant species was House Sparrow (Passer domesticus) (n=156). There were 109 resident species, 43 winter visitors, and 12 summer visitors among the recorded species. Common birds accounted for 41% of the total followed by uncommon birds, Rare birds, and Very Common birds with 33%, 17%, and 9%, respectively. Of the total recorded species, two species were Globally Threatened and nine species were Nationally Threatened. Terrestrial birds had the highest Shannon’s Diversity Index (H=3.97) and Margalef 's Richness Index (R=15.53) whereas wetland birds had the highest Pielou's Evenness Index (E=0.86). The assessment of avian diversity suggests that s Machhaplan Complex offers a suitable habitat for avifauna.